Decadal decline in forest floor soil organic carbon after clear-cutting in Nordic and Canadian forests - C-F. Johannesson; H. Ilvesniemi; O.J. Kjønaas; K.S. Larsen; A. Lehtonen; J. Nordén; D. Paré; H. Silvennoinen; J. Stendahl; I. Stupak; L. Vesterdal; L. Dalsgaard (Forest Ecology and Management, 2025)

Drivers of Interspecific Spatial Segregation in Two Closely‐Related Seabird Species at a Pan‐Atlantic Scale - Anne‐Sophie Bonnet‐Lebrun; Jason Matthiopoulos; Rémi Lemaire‐Patin; Tanguy Deville; Robert Barrett; Maria I. Bogdanova; Mark Bolton; Signe Christensen‐Dalsgaard; Francis Daunt; Nina Dehnhard; Sébastien Descamps; Kyle Elliott; et al. (Journal of Biogeography, 2025)
Aim Ecologically similar species living in sympatry are expected to segregate to reduce the effects of competition where resources are limiting. Segregation from heterospecifics commonly occurs in space, but it is often unknown whether such segregation has underlying environmental causes. Indeed, species could segregate because of different fundamental environmental requirements (i.e., ‘niche divergence’), because competitive exclusion at sympatric sites can force species to either change the habitat use they would have at allopatric sites (i.e., ‘niche displacement’) or to avoid certain areas, independently of habitat (i.e., ‘spatial avoidance’). Testing these hypotheses requires the comparison between sympatric and allopatric sites. Understanding the competitive mechanisms that underlie patterns of spatial segregation could improve predictions of species responses to environmental change, as competition might exacerbate the effects of environmental change. Location North Atlantic and Arctic. Taxa Common guillemots Uria aalge and Brünnich's guillemots Uria lomvia. Methods Here, we examine support for these explanations for spatial segregation in two closely‐related seabird species, common guillemots ( Uria aalge ) and Brünnich's guillemots ( U. lomvia ). For this, we collated a pan‐Atlantic data set of breeding season foraging tracks from 1046 individuals, collected from 20 colonies (8 sympatric and 12 allopatric). These were analysed with habitat models in a spatially transferable framework to compare habitat preferences between species at sympatric and allopatric sites. Results We found no effect of the distribution of heterospecifics on local habitat preferences of the focal species. We found differences in habitat preferences between species, but these were not sufficient to explain the observed levels of spatial segregation at sympatric sites. Main Conclusions Assuming we did not omit any relevant environmental variables, these results suggest a mix of niche divergence and spatial avoidance produces the observed patterns of spatial segregation.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Effects of saccade training on express saccade proportions, saccade latencies, and peak velocities: an investigation of nasal/temporal differences - Ómar I. Jóhannesson; Jay A. Edelman; Bjarki Dalsgaard Sigurþórsson; Árni Kristjánsson (Experimental Brain Research, 2018)

Secondary immune response of rainbow trout following repeated immersion vaccination - R M Jaafar; A Al‐Jubury; J K Chettri; I Dalsgaard; P W Kania; K Buchmann (Journal of Fish Diseases, 2018)
Teleosts are able to raise a protective immune response, comprising both innate and adaptive elements, against various pathogens. This is the basis for a widespread use of vaccines, administered as injection or immersion, in the aquaculture industry. It has been described that repeated injection vaccination of fish raises a secondary immune response, consisting of rapid, accelerated and increased antibody reaction. This study reports how rainbow trout responds to repeated immersion vaccination against yersiniosis ( ERM ) caused by the bacterial pathogen Yersinia ruckeri . It was found that rainbow trout does not raise a classical secondary response following repeated immersion vaccination. Serum antibody titres were merely slightly increased even after three immunizations, using 30‐s immersion into a bacterin consisting of formalin‐inactivated Y. ruckeri (serotype O1, biotypes 1 and 2), performed over a 3‐month period. The densities of IgM‐positive lymphocytes in spleen of fish immunized three times were increased compared to control fish, but no general trend for an increase with the number of immunizations was noted. The lack of a classical secondary response following repeated immersion vaccination may partly be explained by limited uptake of antigen by immersion compared to injection.

In vivo adherence of Flavobacterium psychrophilum to mucosal external surfaces of rainbow trout ( Oncorhynchus mykiss ) fry - A Papadopoulou; I Dalsgaard; A Lindén; T Wiklund (Journal of Fish Diseases, 2017)
The adherence of Flavobacterium psychrophilum to surfaces of epithelial tissues has been inconclusively suggested as a mechanism, which enables the bacterium to invade the host. Hence, the present study aimed to examine the adherence of the cells of two colony phenotypes, smooth and rough, of F. psychrophilum to mucosal tissues of rainbow trout fry and to test the skin mucus as a nutrient for the growth of F. psychrophilum . Fish were immersed in water containing 10 6 CFU mL −1 F. psychrophilum for each colony phenotype. Mucosal tissue samples from fins, gills, skin and eyes, and swab samples from spleen and kidney were taken and inoculated onto TYES agar plates. Colony phenotypes of F. psychrophilum were identified and number of colonies counted. The results showed that cells of both phenotypes initially (0 h) adhered to all mucosal surfaces, but only the rough cells were still present on tissues 1 h post‐immersion. Both phenotypes showed a tissue tropism with the fin tissue being the most adhered. Furthermore, skin mucus promoted the growth of both colony phenotypes. We suggest that the growth of F. psychrophilum cells in skin mucus apparently facilitates the bacterial adherence to mucosal surfaces, and the subsequent invasion into the host.

Circumpolar dynamics of a marine top‐predator track ocean warming rates - Sébastien Descamps; Tycho Anker‐Nilssen; Robert T. Barrett; David B. Irons; Flemming Merkel; Gregory J. Robertson; Nigel G. Yoccoz; Mark L. Mallory; William A. Montevecchi; David Boertmann; Yuri Artukhin; Signe Christensen‐Dalsgaard; et al. (Global Change Biology, 2017)
Global warming is a nonlinear process, and temperature may increase in a stepwise manner. Periods of abrupt warming can trigger persistent changes in the state of ecosystems, also called regime shifts. The responses of organisms to abrupt warming and associated regime shifts can be unlike responses to periods of slow or moderate change. Understanding of nonlinearity in the biological responses to climate warming is needed to assess the consequences of ongoing climate change. Here, we demonstrate that the population dynamics of a long‐lived, wide‐ranging marine predator are associated with changes in the rate of ocean warming. Data from 556 colonies of black‐legged kittiwakes Rissa tridactyla distributed throughout its breeding range revealed that an abrupt warming of sea‐surface temperature in the 1990s coincided with steep kittiwake population decline. Periods of moderate warming in sea temperatures did not seem to affect kittiwake dynamics. The rapid warming observed in the 1990s may have driven large‐scale, circumpolar marine ecosystem shifts that strongly affected kittiwakes through bottom‐up effects. Our study sheds light on the nonlinear response of a circumpolar seabird to large‐scale changes in oceanographic conditions and indicates that marine top predators may be more sensitive to the rate of ocean warming rather than to warming itself.

Positive correlation between Aeromonas salmonicida vaccine antigen concentration and protection in vaccinated rainbow trout Oncorhynchus mykiss evaluated by a tail fin infection model - M H Marana; J Skov; J K Chettri; B Krossøy; I Dalsgaard; P W Kania; K Buchmann (Journal of Fish Diseases, 2017)
Rainbow trout, Oncorhynchus mykiss (Walbaum), are able to raise a protective immune response against Aeromonas salmonicida subsp. salmonicida (AS) following injection vaccination with commercial vaccines containing formalin‐killed bacteria, but the protection is often suboptimal under Danish mariculture conditions. We elucidated whether protection can be improved by increasing the concentration of antigen (formalin‐killed bacteria) in the vaccine. Rainbow trout juveniles were vaccinated by intraperitoneal (i.p.) injection with a bacterin of Aeromonas salmonicida subsp. salmonicida strain 090710‐1/23 in combination with Vibrio anguillarum serotypes O1 and O2a supplemented with an oil adjuvant. Three concentrations of AS antigens were applied. Fish were subsequently challenged with the homologous bacterial strain administered by perforation of the tail fin epidermis and 60‐s contact with live A. salmonicida bacteria. The infection method proved to be efficient and could differentiate efficacies of different vaccines. It was shown that protection and antibody production in exposed fish were positively correlated to the AS antigen concentration in the vaccine.

Detection and quantification of Aeromonas salmonicida in fish tissue by real‐time PCR - S Bartkova; B Kokotovic; H F Skall; N Lorenzen; I Dalsgaard (Journal of Fish Diseases, 2017)
Furunculosis, a septicaemic infection caused by the bacterium Aeromonas salmonicida subsp. salmonicida , currently causes problems in Danish seawater rainbow trout production. Detection has mainly been achieved by bacterial culture, but more rapid and sensitive methods are needed. A previously developed real‐time PCR assay targeting the plasmid encoded aopP gene of A. salmonicida was, in parallel with culturing, used for the examination of five organs of 40 fish from Danish freshwater and seawater farms. Real‐time PCR showed overall a higher frequency of positives than culturing (65% of positive fish by real‐time PCR compared to 30% by a culture approach). Also, no real‐time PCR ‐negative samples were found positive by culturing. A. salmonicida was detected by real‐time PCR , though not by culturing, in freshwater fish showing no signs of furunculosis, indicating possible presence of carrier fish. In seawater fish examined after an outbreak and antibiotics treatment, real‐time PCR showed the presence of the bacterium in all examined organs (1–482 genomic units mg −1 ). With a limit of detection of 40 target copies (1–2 genomic units) per reaction, a high reproducibility and an excellent efficiency, the present real‐time PCR assay provides a sensitive tool for the detection of A. salmonicida .

Infection routes of Aeromonas salmonicida in rainbow trout monitored in vivo by real‐time bioluminescence imaging - S Bartkova; B Kokotovic; I Dalsgaard (Journal of Fish Diseases, 2017)
Recent development of imaging tools has facilitated studies of pathogen infections in vivo in real time. This trend can be exemplified by advances in bioluminescence imaging ( BLI ), an approach that helps to visualize dissemination of pathogens within the same animal over several time points. Here, we employ bacterial BLI for examining routes of entry and spread of Aeromonas salmonicida susbp. salmonicida in rainbow trout. A virulent Danish A. salmonicida strain was tagged with pAK gfplux 1, a dual‐labelled plasmid vector containing the mutated gfpmut3a gene from Aequorea victoria and the lux CDABE genes from the bacterium Photorhabdus luminescens . The resulting A. salmonicida transformant exhibited growth properties and virulence identical to the wild‐type A. salmonicida , which made it suitable for an experimental infection, mimicking natural conditions. Fish were infected with pAK gfplux 1 tagged A. salmonicida via immersion bath. Colonization and subsequent tissue dissemination was followed over a 24‐h period using the IVIS spectrum imaging workstation. Results suggest the pathogen's colonization sites are the dorsal and pectoral fin and the gills, followed by a progression through the internal organs and an ensuing exit via the anal opening. This study provides a tool for visualizing colonization of A. salmonicida and other bacterial pathogens in fish.

Antimicrobial peptide CAP 18 and its effect on Yersinia ruckeri infections in rainbow trout Oncorhynchus mykiss (Walbaum): comparing administration by injection and oral routes - J K Chettri; F Mehrdana; E B Hansen; A Ebbensgaard; M T Overgaard; A H Lauritsen; I Dalsgaard; K Buchmann (Journal of Fish Diseases, 2017)
The antimicrobial peptide CAP 18 has been demonstrated to have a strong in vitro bactericidal effect on Yersinia ruckeri , but its activity in vivo has not been described. In this work, we investigated whether CAP 18 protects rainbow trout Oncorhynchus mykiss (Walbaum) against enteric red mouth disease caused by this pathogen either following i.p. injection or by oral administration (in feed). It was found that injection of CAP 18 into juvenile rainbow trout before exposure to Y. ruckeri was associated with lowered mortality compared to non‐medicated fish although it was less effective than the conventional antibiotic oxolinic acid. Oral administration of CAP 18 to trout did not prevent infection. The proteolytic effect of secretions on the peptide CAP 18 in the fish gastrointestinal tract is suggested to account for the inferior effect of oral administration.

Epidemiological cut‐off values for F lavobacterium psychrophilum MIC data generated by a standard test protocol - P Smith; R Endris; G Kronvall; V Thomas; D Verner‐Jeffreys; C Wilhelm; I Dalsgaard (Journal of Fish Diseases, 2016)
Epidemiological cut‐off values were developed for application to antibiotic susceptibility data for Flavobacterium psychrophilum generated by standard CLSI test protocols. The MIC values for ten antibiotic agents against Flavobacterium psychrophilum were determined in two laboratories. For five antibiotics, the data sets were of sufficient quality and quantity to allow the setting of valid epidemiological cut‐off values. For these agents, the cut‐off values, calculated by the application of the statistically based normalized resistance interpretation method, were ≤16 mg L −1 for erythromycin, ≤2 mg L −1 for florfenicol, ≤0.025 mg L −1 for oxolinic acid (OXO), ≤0.125 mg L −1 for oxytetracycline and ≤20 (1/19) mg L −1 for trimethoprim/sulphamethoxazole. For ampicillin and amoxicillin, the majority of putative wild‐type observations were ‘off scale’, and therefore, statistically valid cut‐off values could not be calculated. For ormetoprim/sulphadimethoxine, the data were excessively diverse and a valid cut‐off could not be determined. For flumequine, the putative wild‐type data were extremely skewed, and for enrofloxacin, there was inadequate separation in the MIC values for putative wild‐type and non‐wild‐type strains. It is argued that the adoption of OXO as a class representative for the quinolone group would be a valid method of determining susceptibilities to these agents.

Effect of hydrogen peroxide and/or F lavobacterium psychrophilum on the gills of rainbow trout, O ncorhynchus mykiss ( W albaum) - M M M Henriksen; P W Kania; K Buchmann; I Dalsgaard (Journal of Fish Diseases, 2015)
The immune response and morphological changes in the gills of rainbow trout fry after immersion in hydrogen peroxide ( H 2 O 2 ), F lavobacterium psychrophilum or combined exposure were examined. The gills were sampled 4, 48, 125 and 192 h after exposure, and the regulation of expression of the following genes was investigated using q PCR : I g T , I g M , CD 8, CD 4, MHC I, MHC II, IL ‐4/13A, T c R ‐β, IL ‐10, IL ‐1β, IL ‐17, SAA and F ox P 3. Bacteria were not observed in haematoxylin‐and‐eosin‐stained gill tissue, but the presence of F . psychrophilum 16 S r RNA was detected using q PCR . The 16 S r RNA levels were correlated with gene expression. Although pretreatment with H 2 O 2 before immersion in F . psychrophilum did not significantly alter the amount of bacteria found in the gill, the immune response was influenced: exposure to F . psychrophilum resulted in a negative correlation with expression of IL ‐17c1, MHC I and MHC II, while pretreatment with H 2 O 2 resulted in a positive correlation with IL ‐4/13 A and I g M . Exposure to either H 2 O 2 or F . psychrophilum influenced the regulation of gene expression and damaged tissue. Exposure to both combined altered the immune response to infection and postponed healing of gill tissue.

Evaluation of the immune response in rainbow trout fry, O ncorhynchus mykiss ( W albaum), after waterborne exposure to F lavobacterium psychrophilum and/or hydrogen peroxide - M M M Henriksen; P W Kania; K Buchmann; I Dalsgaard (Journal of Fish Diseases, 2015)
The immune response in rainbow trout fry against Flavobacterium psychrophilum was elucidated using an immersion‐based challenge with or without prior exposure to hydrogen peroxide (H 2 O 2 ). Samples were taken from the head kidney 4, 48, 125 and 192 h after immersion, and the regulation of several genes was examined. Bacterial load was assessed based on the presence of 16S rRNA and correlated with gene expression, and the levels of specific antibodies in the blood were measured 50 days post‐infection. Separately, both H 2 O 2 and F. psychrophilum influenced gene expression, and pre‐treatment with H 2 O 2 influenced the response to infection with F. psychrophilum . Pre‐treatment with H 2 O 2 also affected correlation between gene regulation and pathogen load for several genes. A delay in antibody production in H 2 O 2 ‐treated fish in the early phase of infection was indicated, but H 2 O 2 exposure did not affect antibody levels 50 days post‐infection. An increasing amount of F. psychrophilum 16S rRNA was found in the head kidneys of infected fish pre‐treated with H 2 O 2 relative to the F. psychrophilum group. The results show that a single pre‐treatment with H 2 O 2 impairs the response against F. psychrophilum and may intensify infection.

Diversity of Flavobacterium psychrophilum and the potential use of its phages for protection against bacterial cold water disease in salmonids - D Castillo; G Higuera; M Villa; M Middelboe; I Dalsgaard; L Madsen; R T Espejo (Journal of Fish Diseases, 2012)
Flavobacterium psychrophilum causes rainbow trout fry syndrome (RTFS) and cold water disease (CWD) in salmonid aquaculture. We report characterization of F. psychrophilum strains and their bacteriophages isolated in Chilean salmonid aquaculture. Results suggest that under laboratory conditions phages can decrease mortality of salmonids from infection by their F. psychrophilum host strain. Twelve F. psychrophilum isolates were characterized, with DNA restriction patterns showing low diversity between strains despite their being obtained from different salmonid production sites and from different tissues. We isolated 15 bacteriophages able to infect some of the F. psychrophilum isolates and characterized six of them in detail. DNA genome sizes were close to 50 Kbp and corresponded to the Siphoviridae and Podoviridae families. One isolate, 6H, probably contains lipids as an essential virion component, based on its chloroform sensitivity and low buoyant density in CsCl. Each phage isolate rarely infected F. psychrophilum strains other than the strain used for its enrichment and isolation. Some bacteriophages could decrease mortality from intraperitoneal injection of its host strain when added together with the bacteria in a ratio of 10 plaque‐forming units per colony‐forming unit. While we recognize the artificial laboratory conditions used for these protection assays, this work is the first to demonstrate that phages might be able protect salmonids from RTFS or CWD.

Chemical surface disinfection of eggs of Baltic cod, Gadus morhua L. - J L Overton; M S Bruun; I Dalsgaard (Journal of Fish Diseases, 2010)
The effect of two disinfectants on eggs and larvae of Baltic cod, Gadus morhua , was investigated. The eggs were disinfected for 10 min using various concentrations of either glutaraldehyde (100, 200, 400, 600 and 800 mg L −1 ) or iodophor (10, 50, 100 and 150 mg L −1 ), 1–4‐days post‐fertilization. Bactericidal effect of disinfection, survival to hatching, hatching success and larval abnormalities were assessed. Larval survival was recorded at 5‐, 10‐ and 15‐days post‐hatch (dph). Although Baltic cod eggs have an unusually thin chorion, they could tolerate surface disinfection. A reduction in bacterial growth was observed with increased concentrations of disinfectant (3.0 × 10 7 –1.6 × 10 1 CFU mL −1 ). Abnormalities in newly hatched larvae were not related to disinfection. Survival of the yolk sac larvae was significantly better for eggs treated with 400 mg L −1 glutaraldehyde for 10 min at 10 and 15 dph. Effective disinfection was also recorded using 100 mg L −1 Actomar K30. Egg batch effect rather than initial bacterial concentration, disinfectant type or incubation method determined the survival of the eggs to hatching and survival of larvae. Because of the carcinogenic effect of glutaraldehyde, iodophor is recommended for routine disinfection of cod eggs.

Water recirculation and good management: potential methods to avoid disease outbreaks with Flavobacterium psychrophilum - L Madsen; I Dalsgaard (Journal of Fish Diseases, 2008)
Flavobacterium psychrophilum infections cause high mortality among rainbow trout, Oncorhynchus mykiss , fry in Danish fish farms and hatcheries. Hatcheries based entirely on bore‐hole water recirculation systems have been suggested as a possibility for eliminating F. psychrophilum or at least keeping the amount of this bacterium low. The occurrence of the bacterium in a bore‐hole water recirculation system was compared with a combined bore‐hole water and stream water flow‐through system in a hatchery where outbreaks of rainbow trout fry syndrome caused by F. psychrophilum often occurred. Broodfish, unfertilized and fertilized eggs, eyed eggs and fry, as well as water samples from the tanks/troughs with broodfish/fry, were examined. Suspect yellow bacterial colonies were either confirmed or rejected as F. psychrophilum by growth characteristics and by PCR. As both virulent and less virulent F. psychrophilum isolates are known, isolates were characterized. The isolates were ribotyped and grouped according to ribotyping patterns. Representatives of the groups were serotyped. Fry isolates were very homogeneous whereas isolates from broodfish were heterogeneous, whether the isolates originated from external surfaces of the fish (mucus from skin and gills, haemorrhages and ulcers) or internal organs. Flavobacterium psychrophilum was isolated from broodfish in both water systems; 56% of investigated broodfish from the borehole/flowthrough system and 36% from the recirculation facility harboured the bacterium. In the recirculation system, the bacterium was isolated from fish (ulcers, milt, liver, abdominal cavity) kept in the system for 11 months. Flavobacterium psychrophilum was found in milt and ovarian fluid as well as on the surface of fertilized eggs, but not inside the eggs. Fry also harboured F. psychrophilum , but in the water recirculation system the bacterium was first isolated from the fry after they had been graded. Flavobacterium psychrophilum was found regularly in other parts of the hatchery (outside the recirculation facility), including at the time of grading, suggesting that the occurrence of F. psychrophilum in the fry recirculation facility was due to contamination from the borehole/flowthrough hatchery. It is suggested that the combination of bore‐hole water recirculation systems and good management procedures (including egg disinfection) is a possible method for hatcheries to avoid disease outbreaks due to F. psychrophilum .

Iron acquisition mechanisms of Flavobacterium psychrophilum - J D Møller; A E Ellis; A C Barnes; I Dalsgaard (Journal of Fish Diseases, 2005)
Forty strains of Flavobacterium psychrophilum were tested for the production of siderophores using the universal Chrome Azurol S (CAS) assay. The majority of the strains (85%) were CAS positive (CAS+) and some (15%) were CAS negative (CAS−). The cryptic plasmid pCP1 was carried by all positive strains and was lacking from negative strains. While a weak catechol reaction was detectable in CAS+ culture supernatants, the CAS reaction was, to some extent, heat sensitive, questioning whether the positive reaction was caused only by siderophores. The ability to grow in vitro under iron‐restricted conditions did not correlate with the CAS reactivity, as growth of both CAS+ and CAS− strains was similarly impaired under iron restriction induced by 2,2 dipyridyl. Suppressed growth under these conditions was restored by addition of FeCl 3 , haemoglobin and transferrin for both CAS+ and CAS− strains.

Flavobacterium psychrophilum in rainbow trout, Oncorhynchus mykiss (Walbaum), hatcheries: studies on broodstock, eggs, fry and environment - L Madsen; J D Møller; I Dalsgaard (Journal of Fish Diseases, 2005)
The occurrence of Flavobacterium psychrophilum at four rainbow trout hatcheries was investigated to provide more knowledge about the reservoirs and transmission of this bacterium. Broodstock were sampled at stripping (including both unfertilized and fertilized eggs), and the offspring were then sampled at the eyed egg and fry stages. Water and surface samples (e.g. hatchery trays) were also sampled. Flavobacterium psychrophilum was found in ovarian fluid and milt, indicating that broodstock may serve as a reservoir and are latent carriers of the pathogen. Flavobacterium psychrophilum was not found on or inside eggs, but further egg studies will be necessary to elucidate the possibility of vertical transmission of the pathogen. Flavobacterium psychrophilum was isolated from water samples, but only from water that had been in close contact with farmed rainbow trout or eggs. Flavobacterium psychrophilum isolates were characterized and compared with well‐characterized strains, using degradation of elastin, serotype and ribotype profiles. Different ribotypes of F. psychrophilum were found between hatcheries, but a common ribotype A was found at all four hatcheries. Different ribotypes were found in broodstock without clinical disease, whereas only a few ribotypes (mostly ribotype A) were found in diseased fry. The same ribotype A was found in broodstock, in water samples from hatchery trays and in fry, which suggests the possibility of transmission of F. psychrophilum between broodstock and offspring.

Phenotypic and genotypic characterization of Flavobacterium psychrophilum from Finnish fish farms - J Madetoja; M‐L Hänninen; V Hirvelä–Koski; I Dalsgaard; T Wiklund (Journal of Fish Diseases, 2001)
Finnish isolates ( n =37) of Flavobacterium psychrophilum isolated from farmed salmonids were studied using phenotypic and genotypic characteristics. The characteristics of isolates were compared with the characteristics of Swedish and Estonian F. psychrophilum isolates and the type strain, F. psychrophilum NCIMB 1947 T . Multiple isolates from eight disease outbreaks were examined to determine differences between isolates from a single outbreak. The F. psychrophilum isolates represented a biochemically homogeneous group. However, some minor differences in biochemical and physiological characteristics were observed. Seven different antigenic patterns among Finnish isolates were detected and the results suggest a new serotype of F. psychrophilum . Using Cla Ι, Hae ΙΙΙ and Pvu ΙΙ restriction enzymes in ribotyping analyses 13 different genotypes were demonstrated and a possible relationship between serotype Fd and genotype F1 was determined. There were no significant differences between the isolates from Finland, Estonia, Sweden and the type strain of F. psychrophilum .

Bacterial pathogens in rainbow trout, Oncorhynchus mykiss (Walbaum), reared at Danish freshwater farms - I Dalsgaard; L Madsen (Journal of Fish Diseases, 2000)
During a 2‐year period, bacterial fish pathogens were monitored on five rainbow trout, Oncorhynchus mykiss (Walbaum), freshwater farms in Denmark. A total of 1206 fish were examined and 361 bacterial isolates were identified phenotypically. Enteric redmouth disease, furunculosis and rainbow trout fry syndrome/coldwater disease were recorded. Infections caused by Flavobacterium psychrophilum occurred most frequently, but only one outbreak of enteric redmouth disease caused by Yersinia ruckeri serotype O1 and one of furunculosis caused by Aeromonas salmonicida were recorded during the monitoring period. Flavobacterium psychrophilum was isolated on all farms, both during disease outbreaks and from fish without any signs of disease. Serological investigations of F. psychrophilum showed that serotype Th was the dominant serotype found. The serotypes Th and Fd were involved in disease outbreaks of fry and larger fish. All isolates of F. psychrophilum showed proteolytic activities; however, a few isolates, belonging to serotype FpT did not degrade elastin and were not associated with mortality. Increasing resistance problems to oxytetracycline were demonstrated. More than half of the F. psychrophilum isolates showed resistance to oxolinic acid and oxytetracycline. No antibiotic resistant isolates were found among Y. ruckeri and A. salmonicida .

Comparative studies of Danish Flavobacterium psychrophilum isolates: ribotypes, plasmid profiles, serotypes and virulence - L Madsen; I Dalsgaard (Journal of Fish Diseases, 2000)
Ribotyping and plasmid profiling were carried out on 299 Danish Flavobacterium psychrophilum isolates from farmed rainbow trout, Oncorhynchus mykiss (Walbaum). The isolates had been characterized biochemically and serologically in another study. The isolates were very homogeneous, 254 isolates had the same ribotype A (restriction enzyme Eco RI) and 284 isolates harboured one 3.3 kb plasmid. Seventy‐five per cent of the F. psychrophilum isolates had ribotype A, one 3.3 kb plasmid and belonged to either serotype Th or Fd. Virulence studies with representatives of the dominant groups classified such isolates as virulent, and an extra small or large plasmid did not change the virulence level. A relationship between the serotypes Fd and Th, certain ribotypes, and virulence was found. The isolates belonging to serotype FpT and to ribotype B were less virulent. Only a few isolates with other ribotypes were found and these were also less virulent. Isolates that did not have the 3.3 kb plasmid were also less virulent. The virulent isolates all harboured the 3.3 kb plasmid; however, there was no clear correlation between virulence and plasmid content as a 3.3 kb plasmid was also found in less virulent isolates.